On Lethal Interactions: Differences Between Expressive and Instrumental Homicides in Mexico City - Meneses-Reyes, Rodrigo (Journal of interpersonal violence, 2021)
Research on violence in Mexico and Latin America suggests that, in part, due to state attempts to fight organized crime and the widespread availability of firearms, violence and homicides in general have experienced a recent shift from expressive to instrumental. Despite this transformation, however, socioeconomically disadvantaged young males continue to be overwhelmingly present in homicide events. We argue that both the use of a firearm and demographic and traditional socioeconomic factors should independently predict instrumental homicide; however, the association between the use of a firearm and instrumentality should be moderated by the level or category of these traditional characteristics (i.e., socioeconomic status, age, and gender). Our findings are broadly consistent with these claims. We show that the relationship between the use of a firearm and instrumental homicides is larger for homicides involving disadvantaged males as victims because this group is more at risk of suffering homicidal violence to begin with, despite the fact that independently (i.e., with no interactions), higher socioeconomic status, age, and female victimhood are positively associated with instrumentality. We discuss the implications of these findings for research on Latin American violence and the expressive/instrumental distinction.